Efficient in vivo neuronal genome editing in the mouse brain using nanocapsules containing CRISPR-Cas9 ribonucleoproteins. (February 2023) - Metzger, Jeanette M.; Wang, Yuyuan; Neuman, Samuel S.; Snow, Kathy J.; Murray, Stephen A.; Lutz, Cathleen M.; Bondarenko, Viktoriya; Felton, Jesi; Gimse, Kirstan; Xie, Ruosen; Li, Dongdong; Zhao, Yi; et al.
Abstract: Genome editing of somatic cells via clustered regularly interspaced short palindromic repeats (CRISPR) offers promise for new therapeutics to treat a variety of genetic disorders, including neurological diseases. However, the dense and complex parenchyma of the brain and the post-mitotic state of neurons make efficient genome editing challenging. In vivo delivery systems for CRISPR-Cas proteins and single guide RNA (sgRNA) include both viral vectors and non-viral strategies, each presenting different advantages and disadvantages for clinical application. We developed non-viral and biodegradable PEGylated nanocapsules (NCs) that deliver preassembled Cas9-sgRNA ribonucleoproteins (RNPs). Here, we show that the RNP NCs led to robust genome editing in neurons following intracerebral injection into the healthy mouse striatum. Genome editing was predominantly observed in medium spiny neurons (>80%), with occasional editing in cholinergic, calretinin, and parvalbumin interneurons. Glial activation was minimal and was localized along the needle tract. Our results demonstrate that the RNP NCs are capable of safe and efficient neuronal genome editing in vivo .